Pharmacophore-based virtual screening approaches to identify novel molecular candidates against EGFR through comprehensive computational approaches and in-vitro studies - Opo, F A Dain Md; Moulay, Mohammed; Zari, Ali; Alqaderi, Afnan; Alkarim, Saleh; Zari, Talal; Bhuiyan, Mohiuddin Ahmed; Mahmoud, Maged Mostafa; Aljoud, Fadwa; Suhail, Mohd; Edris, Sherif; Ramadan, Wafaa S.; et al. (Frontiers in Pharmacology, 2022)
Alterations to the EGFR (Epidermal growth factor receptor) gene, which primarily occur in axon 18–21 position, have been linked to a variety of cancers, including ovarian, breast, colon, and lung cancer. The use of TK inhibitors (gefitinib, erlotinib, lapatinib, and afatinib) and monoclonal antibodies (cetuximab, panitumumab, and matuzumab) in the treatment of advanced-stage cancer is very common. Using these drugs are becoming less effective in EGFR targeted cancer treatment and developing resistance to cancer cell eradication, which sometimes necessitates stopping treatment due to the side effects. One in-silico study has been conducted to identify EGFR antagonists by using other compounds, databases without providing the toxicity profile, comparative analysis, or morphological cell death pattern. The goal of our study was to identify potential lead compounds, and we identified seven compounds based on the docking score as well as four that were chosen for our study utilizing toxicity analysis. Molecular docking, virtual screening, dynamic simulation, and in-vitro screening indicated that these compounds' effects were superior to already marketed medication (gefitinib). The four compounds obtained, ZINC96937394, ZINC14611940, ZINC103239230, and ZINC96933670, demonstrated improved binding affinity (-9.9 kcal/mol, -9.6 kcal/mol, -9.5 kcal/mol and -9.2 kcal/mol), interaction stability, and a lower toxicity profile. In-silico toxicity analysis showed that our compounds have a lower toxicity profile and a higher LD50 value. At the same time, a selected compound, i.e., ZINC103239230, was revealed to attach to a particular active site and bind more tightly to the protein, as well as better in-vitro results when compared to our selected gefitinib medication. MTT assay, gene expression analysis (BAX, BCL-2, β-catenin), apoptosis analysis, TEM, cell cycle assay, ELISA, cell migration assays were conducted to find the cell death analysis of lung cancer, breast cancer comparing to the marketed product. The MTT assay exhibited 80% cell death for 75µM and 100µM, however flow cytometry analysis with the IC50 value demonstrated that the selected compound induced apoptosis higher in MCF-7 (30.8%) rather than in A549.